2015
DOI: 10.1130/ges01152.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic deep-water circulation in the northwestern Pacific during the Eocene: Evidence from Ocean Drilling Program Site 884 benthic foraminiferal stable isotopes (δ18O and δ13C)

Abstract: New benthic foraminiferal δ 18 O and δ 13 C data from Ocean Drilling Program (ODP) Site 884 (northwestern Pacific) add significant structure to a previous lower resolution record; our higher resolution detail and comparisons with published isotopic records provide new insights into paleoceanographic changes in the northwestern Pacific from the middle Eocene to the early Oligocene. From the early-middle until the mid-middle Eocene (ca. 49-43 Ma), a comparison of the Site 884 δ 18 O values with published ODP δ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 116 publications
0
17
0
Order By: Relevance
“…The possibility that a deep water mass began to form around Antarctica in the late Eocene (ca. 36.5 Ma) and subsequently spread into the North Pacific is supported by the gradual increase of the oxygen isotope ratios of benthic foraminifera (δ 18 O bf ) over a period of about 2.5 million years 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that a deep water mass began to form around Antarctica in the late Eocene (ca. 36.5 Ma) and subsequently spread into the North Pacific is supported by the gradual increase of the oxygen isotope ratios of benthic foraminifera (δ 18 O bf ) over a period of about 2.5 million years 25 .…”
Section: Discussionmentioning
confidence: 99%
“…From the middle to late Eocene, the opening of the Southern Ocean Gateways-the Drake Passage and Tasman Rise-led to the development of a current around Antarctica shallower than the present Antarctic Circumpolar Current (ACC), the so-called proto-ACC 2,25 . The possibility that a deep water mass began to form around Antarctica in the late Eocene (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Current research suggests that Southern Ocean sourced bottom water was flowing into the northern Pacific Ocean as early as the late Eocene [ Borrelli and Katz , ]. Furthermore, a modern‐layered ocean structure developed during the early Oligocene (~30 Ma) [ Katz et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…This was occurring at a time when equatorial seaways (i.e., Panama and Tethys) were still open, allowing water mass flow from the Atlantic to Pacific Oceans. Foraminiferal studies have suggested a warm, saline deepwater mass existed during the Eocene and Oligocene in the Atlantic and Pacific Oceans and had a low‐latitude source [ Borrelli and Katz , ; Kennett and Stott , ; Langton et al , ; Mead et al , ; Pak and Miller , ; Pekar et al , ; Via and Thomas , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation